A Simplified Fluoroscopic Method for Commissural Alignment Assessment With a Balloon-Expandable Transcatheter Heart Valve - Mariama Akodad, MD, PhD; David Meier, MD; Georgios Tzimas, MD; Jonathon Leipsic, MD; Philipp Blanke, MD; David A. Wood, MD; John G. Webb, MD; Janarthanan Sathananthan, MB ChB, MD (JACC: Case Reports, 2023)
We sought to assess commissural alignment of the balloon-expandable valve on fluoroscopy. Commissural alignment was defined on fluoroscopy in 20 patients according to alignment of the valve commissural posts in the 3-cusp and the cusp-overlap view and correlated with post–transcatheter aortic valve replacement computed tomography. Agreement was strong between computed tomography and fluoroscopy (weighted Cohen’s kappa coefficient: 0.88). (Level of Difficulty: Advanced.)